1973
DOI: 10.1111/j.1476-5381.1973.tb08168.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an isolated toxin from Australian Tiger snake (Notechis scutatus scutatus) venom at the mammalian neuromuscular junction

Abstract: Summary The acute effects of a purified toxin from Australian Tiger snake (Notechis scutatus scutatus) venom have been investigated at the mammalian neuromuscular junction. The toxin was injected into the tail vein of mice. Death was due to respiratory paralysis. The resting membrane potential, and action potential of muscle fibres in muscles from in vivo intoxicated animals were normal. The frequency of miniature end plate potentials (m.e.p.p.s) from intoxicated nerve‐muscle preparations was reduced, althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

1976
1976
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(37 citation statements)
references
References 13 publications
(14 reference statements)
2
35
0
Order By: Relevance
“…Unlike the venoms of the tiger snake, Notechis scutatus and the taipan, Oxyuranus scutellatus which have clearly demonstrated presynaptic activity (Datyner & Gage, 1973;Harris et al, 1973;Kamenskaya & Thesleff, 1974) The apparent lack of myotoxicity of the venom has been confirmed in the monkey by Sutherland & Campbell (1980) but the apparent lack of presynaptic activity is possibly contentious. Coulter, Broad & Sutherland (1980) have isolated a high molecular weight protein (textilon) from the crude venom of Pseudonaja textilis, and preliminary studies by Southcott & Coulter (1980) have suggested that it is a presynaptically active neurotoxin.…”
Section: Endplate Potentials Endplate Potentials (Epps)mentioning
confidence: 92%
“…Unlike the venoms of the tiger snake, Notechis scutatus and the taipan, Oxyuranus scutellatus which have clearly demonstrated presynaptic activity (Datyner & Gage, 1973;Harris et al, 1973;Kamenskaya & Thesleff, 1974) The apparent lack of myotoxicity of the venom has been confirmed in the monkey by Sutherland & Campbell (1980) but the apparent lack of presynaptic activity is possibly contentious. Coulter, Broad & Sutherland (1980) have isolated a high molecular weight protein (textilon) from the crude venom of Pseudonaja textilis, and preliminary studies by Southcott & Coulter (1980) have suggested that it is a presynaptically active neurotoxin.…”
Section: Endplate Potentials Endplate Potentials (Epps)mentioning
confidence: 92%
“…For example, the snake neurotoxin crotoxin is composed of a PLA 2 subunit and an inhibitory subunit, which keeps the phospholipase inactive until binding to a presynaptic receptor triggers the dissociation of the inhibitory subunit (30). In contrast, notexin from Netechis scutatus scutatus is a PLA 2 without an associated subunit that produces muscle paralysis by binding to a specific receptor in the neuromuscular junction (31). IpTx i is the first example of a scorpion toxin in which a PLA 2 is found chaperoned by a smaller, structurally unrelated subunit.…”
Section: Discussionmentioning
confidence: 99%
“…cells [2,14] which is probably related to the neurotoxicity, and this function is not greatly diminished after modification with p-bromophenacyl bromide [ 151. The loss of lethality attending the chemical modification might reflect a loss of specificity, possibly as a result of the impaired ability to bind calcium.…”
Section: Discussionmentioning
confidence: 99%
“…Notexin from the venom of Notechis scutatus scutatus is a basic protein with 119 amino acid residues and seven disulfide bridges which blocks neuromuscular transmission by interfering with the release of acetylcholine from the motor nerve terminals [ 1,2] . Notexin exhibits phospholipase activity and is highly homologous to phospholipase A from porcine pancreas and various snake venoms , raising the possibility that the neurotoxicity is catalytic in nature, involving the hydrolysis of a special phospholipid structure in the nerve terminal.…”
Section: Introductionmentioning
confidence: 99%